FENOMENA SOSIAL DALAM PENDIDIKAN DAN ISU-ISU SOSIAL BUDAYA - Nova Riza; Marsiyeh; Ubabuddin (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
This article explains social phenomena in education and socio-cultural issues. Social phenomena are all symptoms or events that can be observed and studied in social life or social science. Social phenomena are facts that emerge in society as a result of interactions between individuals or groups in society. Social culture is all the values that apply in a society which are characteristics of the society itself. This means that social culture is a dynamic in society, including in education. This research study uses a literature review in which the literature is taken according to the subject matter and analyzed in depth so that conclusions and findings in the research can be drawn. Literature taken from books and journals.